APLIKASI TRAINMEASURE PERJALANAN KERETA API DENGAN ALGORITHMA DIJKSTRA UNTUK MENGUKUR JARAK STASIUN TERDEKAT BERBASIS ANDROID - Fitri Latifah; Andri Prasetyo (Jurnal Techno Nusa Mandiri, 2015)
Travel by train to use the cities on the island of Java became one of the current public transportation options. In the course of passenger trains often have to want to know where his journey and also how much longer to arrive at the destination station. The development of information technology one can help provide information to passengers about the train position and also a journey that must be taken to arrive at the station where the journey tujuan.ai and also how much longer to arrive at the destination station. The widespread use of smartphones due to a more affordable price. Making everyone can have it. With the application of "Trainmeasure" is expected to help provide the information needed passenger trains. Especially on a trip distance and travel time.